Teaching and learning during "Old Normal" and "New Normal": Justifications, modifications, and lessons learnt - Soubakeavathi, Rethinasamy; Ramanair, Joseph (CALM UNIMAS, 2020)
Teaching, learning and assessment activities are crucial part of a course delivery in educational institutions. While face-to-face (F2F) teaching remains as an important component of teaching and learning, blended and online learning have grown progressively over the past few years and become an essential part of educational institutions around the globe. In 2020 the need to deliver courses fully online was suddenly amplified by the movement control measures implemented due to the COVID-19 pandemic. The pandemic has forced the courses which were taught F2F or in a blended manner, to be taught fully online. This sole online teaching approach requires some significant changes to not only the course delivery but also every aspect of teaching and learning.